2017
DOI: 10.4103/0976-0105.195083
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Clinical Pharmacy Activity in a Pediatric Inpatient Department in Cote D′ivoire

Abstract: Background:Clinical pharmacy activities in a pediatric inpatient department help to improve the management of patients clinically and economically.Objective:To assess the relevance of pharmaceutical interventions (PIs) in a pediatric inpatient department in Abidjan (Cote d’Ivoire).Materials and Methods:We carried out a cross-sectional, descriptive study from February to September 2014. The information collected was classified according to the classification of drug-related problems (DRPs) and PIs of the French… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
(30 reference statements)
6
18
0
Order By: Relevance
“…Based on this classification system, anti-infectives for systemic use (ATC group J) was the most common (30.7%) drug class associated with DRPs in this study. is finding is in agreement with other studies done in patients with hematology malignancies [37] as well as other patients [22,24,30,31,38]. Anti-infective drugs encompass the largest number of drug classes widely prescribed in TASH and associated with DRPs needing pharmaceutical interventions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on this classification system, anti-infectives for systemic use (ATC group J) was the most common (30.7%) drug class associated with DRPs in this study. is finding is in agreement with other studies done in patients with hematology malignancies [37] as well as other patients [22,24,30,31,38]. Anti-infective drugs encompass the largest number of drug classes widely prescribed in TASH and associated with DRPs needing pharmaceutical interventions.…”
Section: Discussionsupporting
confidence: 92%
“…e addition of a drug, which accounted for about 31.4%, was the most common recommendation made, and this is consistent with an Indian study (29.3%) [27]. e second most common intervention recommended was dose adjustment (30.2%), and a similar rate was also reported in a Cote d'Ivoire study (32%) [31]. Interventions were fully accepted in 223 (92.15%) and not accepted in 10 (4.13%) of the cases.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The other antibiotics in this group were rifampicin (33.3%) and isoniazid (16.7%). Abrogoua et al [9,10] conducted a study on pharmacist intervention in outpatient prescriptions and found that the proportion of drug-related problems involving a subtherapeutic dose was 11.1%; the antibiotic that was most frequently involved was amoxiclav (61.9%).…”
Section: Description Of Prescribed Medicinementioning
confidence: 99%